Kritik terhadap Ideologi Pembangunan: Perspektif Epistemicide Boaventura de Sousa Santos - Krisnadi, Leonardus Aditya (Jurnal Filsafat Indonesia, 2023)
This study aims to explain criticism of developmentalism with Boaventura de Sousa Santos’ epistemicide theory. This study used the philosophy hermeneutic method. Boaventura de Sousa Santos’ epistemicide theory exposed the long history of Western epistemology’s domination over non-Western epistemologies. In the past, colonialism and imperialism used epistemicide to murder local knowledge in order to create Western epistemological supremacy. Today, epistemicide is used to justify developmentalism, where developing countries are directed to follow certain guidelines to reach modernity like Western civilization. Developmentalism has become a new form of Western domination over developing countries by eliminating local knowledge. In the end, the loss of knowledge will be contributed to the loss of local people’s control over the future of their nation. To overcome the impact of epistemicide, Santos offers 2 procedures: the ecology of knowledge and intercultural translation. Both of these procedures encourage the realization of an alternative epistemology based on recognition of domination and encourage respect for the epistemology diversity.